Public Interest Sebagai Sumber Hukum Islam: Studi Terhadap Konsepsi Al Maslahah Najm al-Din al-Tufi - M. Nur Agus Salim (Justicia Islamica, 2009)
This study aims to examine the concept of public interest as a source of Islamic law through Najm al-Din al-Tufi's thinking on al-maslahah. The method used is qualitative with a normative-philosophical approach, through a literature study of al-Tufi's works and classical and contemporary Islamic legal literature. The results of the study show that al-Tufi places al-maslahah as an independent source of law that can override other arguments in a particular social context, especially in the realm of muamalah and socio-politics. This concept is considered progressive because it emphasizes the flexibility of sharia in responding to the needs and interests of the ummah. This study concludes that al-Tufi's ideas provide ample room for ijtihad for the formation of Islamic law that is contextual, relevant, and responsive to the dynamics of the times.